Pilot Production of Mesenchymal Stem/Stromal Freeze-Dried Secretome for Cell-Free Regenerative Nanomedicine: A Validated GMP-Compliant Process - Elia Bari; Sara Perteghella; Dario Di Silvestre; Marzio Sorlini; Laura Catenacci; Milena Sorrenti; Giorgio Marrubini; Rossana Rossi; Giuseppe Tripodo; Pierluigi Mauri; Mario Marazzi; Maria Luisa Torre (Cells, 2018)
In this paper, a pilot production process for mesenchymal stem/stromal freeze-dried secretome was performed in a validated good manufacturing practice (GMP)-compliant cell factory. Secretome was purified from culture supernatants by ultrafiltration, added to cryoprotectant, lyophilized and characterized. We obtained a freeze-dried, “ready-off-the-shelf„ and free soluble powder containing extracellular vesicles and proteins. In the freeze-dried product, a not-aggregated population of extracellular vesicles was detected by nanoparticle tracking analysis; Fourier transform infrared spectra showed the simultaneous presence of protein and lipids, while differential scanning calorimetry demonstrated that lyophilization process successfully occurred. A proteomic characterization allowed the identification of proteins involved in immune response, response to stress, cytoskeleton and metabolism. Moreover, the product was not cytotoxic up to concentrations of 25 mg/mL (on human fibroblasts, chondrocytes and nucleus pulposus cells by MTT assay) and was blood compatible up to 150 mg/mL. Finally, at concentrations between 5 and 50 mg/mL, freeze-dried secretome showed to in vitro counteract the oxidative stress damage induced by H2O2 on nucleus pulposus cells by MTT assay.